Case Report: Atonic PNES Capture in fMRI - Hologne, Emmanuelle; Hossu, Gabriela; Fantin, Luca; Braun, Marc; Husson, Cyril; Tyvaert, Louise; Hingray, Coraline (Frontiers in Neurology, 2022)
Psychogenic Non Epileptic Seizures (PNES) are a misunderstood and disabling pathology, characterized by a paroxysmal occurrence of clinical signs without epileptic activity. Resting-state functional Magnetic Resonance Imaging (fMRI) studies in PNES patients have shown abnormal functional connectivity of the resting-state networks, especially in the limbic and motor systems, and in the precuneus. However, the transient nature of PNES episodes prevents us from elucidating underlying mechanisms of seizures. Here, we report the case of a patient who presented an atonic episode of PNES during a 3T fMRI session. The patient is a 23-year-old woman, suffering from Post-Traumatic Stress Disorder, with no neurological comorbidities. The preprocessing of the fMRI images involved realignment, coregistration, segmentation, normalization, denoising (PhysIO toolbox) and smoothing. The time boundary of the seizure was defined according to the patient’s reports, and seizure period was contrasted with the resting state period before the seizure. A whole-brain analysis showed significant activations (left inferior temporal gyrus; left temporo-occipital junction) and deactivations (right precuneus, right superior parietal lobule, right postcentral gyrus, bilateral lingual gyri, inferior occipital gyri and cerebellar lobules; right insula in subthresholded analysis). Activations and deactivations occurred in four cerebral networks: emotional processing, agency, self-perception and dissociation. To our knowledge, this report is the first published case of functional imaging during PNES. These results could confirm the emotional and dissociative hypothesis of the physiopathology of PNES and highlight future targets for neuromodulation.